Craftsman, informal heritage management and social capital in conserving chini-tikri work of Kosaituli mosque, Old Dhaka, Bangladesh - Ahmed, Iftekhar (Journal of cultural heritage management and sustainable development, 2019)
PurposeThe purpose of this paper is to present a community-led “informal heritage management” of the chini-tikri work of Kosaituli mosque, Old Dhaka, Bangladesh. It critically explores the interrelationship between the craft, existing social capital and informal heritage management.Design/methodology/approachThis paper assesses the existing local policies, strategies and the top-down conservation efforts led by government and identifies the shortcomings. The study uses Kosaituli mosque as a case study as it displays some of the finest surviving examples of the chini-tikri work. Using observation, open-ended interview and focus group discussion as research tools, the study explores the challenges that the craft and craftsman faces, how existing social capital supports the informal heritage management process and the interrelationship between these critical elements.FindingsThe results shows two clear issues. First, the informal heritage management system has been continuing to protect and manage the local heritage while fighting several challenges. Second, though they require external support, they want to keep the “community ownership.” The study recommends how the craftsman can be revived through incentives and capacity building to facilitate the survival of the craft with a three-step process: identifying the rare craftsmen, providing them due recognition and transferring the traditional knowledge to the next generation.Originality/valueNo similar prior studies were carried out in Old Dhaka that focus on this subject. This paper can contribute in new policy formation not only for Bangladesh but also will potentially guide other cities that face similar challenges of disappearing craft and craftsman.